Identification of sex‐specific biomarkers predicting new‐onset heart failure. (22nd June 2021) - Raafs, Anne; Verdonschot, Job; Ferreira, João Pedro; Wang, Ping; Collier, Timothy; Henkens, Michiel; Björkman, Jens; Boccanelli, Alessandro; Clark, Andrew L.; Delles, Christian; Diez, Javier; González, Arantxa; et al.
Abstract: Aims: Heart failure (HF) is common in both men and women, yet disease pathophysiology, presentation, and progression differ between sexes. Studies addressing whether biomarkers predict new onset HF sex‐specifically are scarce. This study therefore aims to test the sex‐specificity of 252 protein biomarkers for new‐onset HF. Methods and results: A matched case–control design in patients selected from cohorts within the HOMAGE consortium was used. Cases (new‐onset HF, n = 562) and controls ( n = 780) were matched for cohort (PREDICTOR, HEALTH‐ABC, & PROSPER), follow‐up time (defined as time from entry to incident HF), and age. Incident HF was defined as first hospitalization for HF. Targeted plasma proteins ( n = 252) were measured using Proximity Extension Assay technology from O‐link. To look for sex differences for new onset HF, we adjusted for cohort, age, and baseline clinical parameters. At baseline, women had a biomarker profile reflecting activated metabolism and immune responses. However, none of the biomarkers had a significant interaction with sex in predicting new onset HF, but four biomarkers had a trend towards sex‐specificity ( P < 0.013). E‐selectin and interleukin 1 receptor antagonist were more female‐specific, whereas IL17A and CHIT1 tended to be male sex‐specific for incident HF. Conclusions: The majority of biomarkers associated with incident HF did not significantly differ between women and men, despite clear differences in biomarkers at baseline.